Smart waste bins - Muhammad Amali, Nurul Afni; Othman, Muhammad Baihaki; Setapa, Mariam; Kamarul Zaman, Liziana; Wan Mustapha, Wan Asma Hanim; Mohamed, Firdawati; Abdullah@Adnan, Norshaieda (Universiti Teknologi MARA, Perak, 2023)
The purpose of this study is to design and develop a smart waste bin that utilizes innovative technology to improve waste management practices. The study employed a design and development methodology to create a framework for the smart waste bin. To reduce reliance on traditional sources of energy, solar panels were added to offer sustainable power for its operations. To increase the capacity of the bin, improve waste collection efficiency, and lessen the need for frequent emptying, waste compaction technology was added. Furthermore, real-time trash level monitoring utilizes sensors and data analytic to enable accurate estimations of bin fill levels. This information can be utilized to optimize waste collection routes, leading to cost savings and reduced environmental impact.The smart waste bins come in different sizes, catering to the diverse needs of various environments and users. Additionally, the advertisement panels present an opportunity for organizations and municipalities to generate revenue by displaying relevant advertisements or public messaging. Moreover, the smart waste bin is designed with a 3 bins system to segregate different categories of waste such as organic waste, reject and dry waste. Reject waste refers to non-biodegradable waste including diapers, sanitary pads, bulbs and ewaste. This kind of waste will finally end up in landfills. However, organic waste will be turning up into compost and dry waste is undergoing a recycling process. The smart waste bin is an innovative solution for waste management that can help reduce waste overflow, improve cleanliness, and reduce the frequency of waste collection. The real-timetrash level monitoring feature allows for efficient waste collection and management, while the advertisement panels provide an opportunity for revenue generation and with 3 Bins System. The smart waste bin has practical implications for waste management practices in public spaces, such as parks, streets, and commercial areas. It can help reduce the workload of waste management personnel and improve the overall cleanliness of public spaces. A special and innovative alternative that combines several features to enhance waste management procedures is the smart waste bin. It is a useful addition to the current waste management infrastructure and can lessen waste overflow and boost waste collection efficiency all around.